Regulation of cargo‐selective endocytosis by dynamin 2 GTPase‐activating protein girdin. (24th July 2014) - Weng, Liang; Enomoto, Atsushi; Miyoshi, Hiroshi; Takahashi, Kiyofumi; Asai, Naoya; Morone, Nobuhiro; Jiang, Ping; An, Jian; Kato, Takuya; Kuroda, Keisuke; Watanabe, Takashi; Asai, Masato; et al.
Abstract In clathrin‐mediated endocytosis (CME), specificity and selectivity for cargoes are thought to be tightly regulated by cargo‐specific adaptors for distinct cellular functions. Here, we show that the actin‐binding protein girdin is a regulator of cargo‐selective CME. Girdin interacts with dynamin 2, a GTPase that excises endocytic vesicles from the plasma membrane, and functions as its GTPase‐activating protein. Interestingly, girdin depletion leads to the defect in clathrin‐coated pit formation in the center of cells. Also, we find that girdin differentially interacts with some cargoes, which competitively prevents girdin from interacting with dynamin 2 and confers the cargo selectivity for CME. Therefore, girdin regulates transferrin and E‐cadherin endocytosis in the center of cells and their subsequent polarized intracellular localization, but has no effect on integrin and epidermal growth factor receptor endocytosis that occurs at the cell periphery. Our results reveal that girdin regulates selective CME via a mechanism involving dynamin 2, but not by operating as a cargo‐specific adaptor.